Uma proposta de educação para o campo : Casa Familiar Rural Padre Haruo Sasaki - Alexandre, Bruno Henrique Gomes (2008)
It is said for a long time in the estimated theoreticians of grades to school resumes, for developing a pedagogical practice related to knowledge historically constructed for the society and toward the reality lived for the students. The Brazilian educational trajectory, particularly of the agricultural population, reveals historically abandoned, due to few referring experiences to this statement. The implantation of the neoliberal educational politics, in fact, is against of this principle, therefore the universalization of education, seen as advance in the last years, did not guarantee the improvement of the quality of education and, the investments in the education are limited and insufficient for a reorganization of the form resume to take care of the real necessities of the students, particularly of the agricultural schools. Perhaps the pedagogy of the alternation, object of this research, is an exception. It aims to analyze the peculiarities of this proposal in the state of Paraná, especially in the city of Sapopema, and study how this form of curricular organization influences the pedagogical practice and the improvement of the quality of students' life guaranteeing them the staying in the agricultural life and access the new technologies and the citizenship, through actions that search for changes in the reality, according to a sustainable development in familiar agriculture.